PECTIN THERAPY IS A METHOD OF PREVENTION OF REPRODUCTIVE LOSSES ASSOCIATED WITH INTRAPLACENTARY ACCUMULATION OF RADIONUCLIDES - А. Живецька- Денисова; І. Воробйова; Н. Скрипченко; Л. Лозова; О. Шамаєва; Н. Рудакова; С. Стрижак (Неонатологія, хірургія та перинатальна медицина)
To date, environmental factors play a decisive role in the pathogenesis of miscarriage. The ecology of Ukraine suffered due to the accident at the Chornobyl NPP, which has no analogs in terms of the number of radionuclides that entered the environment, the area affected, and the consequences. In modern conditions, people are exposed to radioactive substances through food. Among the 200 radionuclides that have entered the environment, 137Cs represent the greatest danger in the long term due to soil and water contamination. Internal radiation is one of the causes of reproductive losses. The accumulation of 137Cs in the placenta disrupts its architecture, functionality, and peroxide hemostasis. Detox defects due to 137Cs require correction to prevent reproductive losses.